PERANCANGAN APLIKASI PENCATATAN ZAKAT BERBASIS WEB MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT STUDI KASUS MUSHOLLA AL-HIDAYAH: DESIGN OF A WEB-BASED ZAKAT RECORDING APPLICATION USING THE RAPID APPLICATION DEVELOPMENT METHOD A CASE STUDY AT MUSHOLLA AL-HIDAYAH - Sadham Alwie; Ifan Junaedi; Anton Zulkarnain Sianipar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This This study aims to design and develop a web-based zakat recording application for Musholla Al-Hidayah., zakat recording is done manually using notebooks, which can lead to recording errors, data loss, and inefficiencies in management. The Rapid Application Development (RAD) method is used to address these issues, allowing a fast and iterative development process with direct user feedback. Data were collected through observation, interviews, and literature review. The application includes main features such as login, dashboard, zakat recording, zakat receipt, and zakat reporting. Based on black-box testing, the application has 7 main features with a total of 17 test scenarios, all of which successfully functioned 100% as expected. This application is designed to assist the management in recording zakat data from residents of three neighborhood units, namely RT 10, RT 11, and RT 12, which were previously recorded manually in the area of Jl. Matraman Dalam III, Central Jakarta. Consequently, the process of recording, reporting, and managing zakat becomes faster, more organized, and more efficient.